Capital Mobility within EMU - Claudia Stirböck; Friedrich Heinemann (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
Capital mobility is helpful to cope with the loss of adjustment instruments in EMU. High capital mobility in the sense of Feldstein and Horioka (FH) can limit the negative consequences of shocks affecting the saving capacity of an economy in the Eurozone. It is the aim of this paper to assess the likely degree of capital mobility in the FH sense within EMU. For this purpose, the FH approach is extended and updated. In particular, the role of current account targeting, exchange rate volatility and tax differentials as potential obstacles to capital mobility is analyzed. The empirical findings support the view that both current account targeting and exchange rate volatility were relevant for limiting the free flow of capital in the past. The conclusion is that within EMU domestic saving and investment will be less correlated than they were before the advent of the Euro.
Keywords: F36; F21; 330; Capital Mobility; European Monetary Union; Investment-Saving-Relation; Internationale Kapitalmobilität; Europäische Wirtschafts- und Währungsunion; Investition; Sparen; Schätzung; EU-Staaten; Feldstein-Horioka